Pembentukan Karakter Melalui Peran Pendidikan Agama Islam Di Era Revolusi Industri - Mohamad Wahyudin; Zaenuri; Dedy Yansyah; Sucihati (UNISAN JURNAL, 2024)
This examination expects to portray character development through the job of Islamic strict schooling in the time of the modern transformation. This exploration utilizes subjective techniques with the kind of library research. Analysts dissected composed writing as the fundamental source as books, research diaries and course procedures. The consequences of this examination show that schooling is something that can’t be isolated from day to day existence, particularly in shaping great character qualities. Islamic strict training as schooling that depends on the development of ethics and character is the fundamental objective in schooling. In this way, character development in the execution of training is brought out through educating, adjustment, model, pressure and discipline which empower and shape the personality of understudies. Schooling assumes a significant part, particularly in learning Islamic strict training, where it has an extraordinary impact in decreasing and stifling adolescent misconduct and assumes a part in assisting with molding the personality of understudies in the ongoing millennial time, on the grounds that Islamic strict instruction puts more prominent accentuation on imparting virtues. With the fervor of the data innovation based training process, a learning idea that stresses the development of ethics, a strict character, and worry for the climate is vital to be aimed at reinforcing the personality of understudies, which is the objective of public instruction.